Fast Look. The sightseeing ritual in monumental cities - Espelt, Nuria Gali; Donaire, Jose Antonio (RITUR - Revista Iberoamericana de Turismo, 2021)
This article contends and conceptualizes that the ritual of sightseeing and the relationship between tourists and tourist attractions in monumental cities is highly predictable and repetitive. Visitors in monumental cities show patterns of a mimetic behaviour. This ritual, which we call “fast look” (an analogy with fast food), has three features: (a) the low number of tourist attractions visited compared to the number that could potentially be visited; (b) the high number of visits to particular tourist attractions, as the majority of visitors choose to visit the same spaces; and (c) the short time, on average, spent on visiting each attraction. The features underpinning “fast look” are supported in this case study